2019
DOI: 10.1002/mgg3.883
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between conventional and comprehensive sequencing approaches for genetic diagnosis of Alport syndrome

Abstract: Background Alport syndrome (AS) is a hereditary disease caused by mutations in COL4A3‐5 genes. Recently, comprehensive genetic analysis has become the first‐line diagnostic tool for AS. However, no reports comparing mutation identification rates between conventional sequencing and comprehensive screening have been published. Methods In this study, 441 patients clinically suspected of having AS were divided into two groups and compared. The initial mutational analysis method involved targeted exome sequencing u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
1
25
1
1
Order By: Relevance
“…Due to the increased availability of NGS, the number of reports of ADAS is rapidly increasing [9,10,34]. For example, Yamamura et al performed genetic analysis for 390 families with suspicion of AS and showed that XLAS represented 74% of the cases, ARAS 9%, and ADAS 17%, which was notably higher than previously reported [10]. However, some experts still question the diagnosis of ADAS [14].…”
Section: Establishment Of the Concept Of Adasmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the increased availability of NGS, the number of reports of ADAS is rapidly increasing [9,10,34]. For example, Yamamura et al performed genetic analysis for 390 families with suspicion of AS and showed that XLAS represented 74% of the cases, ARAS 9%, and ADAS 17%, which was notably higher than previously reported [10]. However, some experts still question the diagnosis of ADAS [14].…”
Section: Establishment Of the Concept Of Adasmentioning
confidence: 99%
“…Although ADAS was thought to be an extremely rare disease and its disease concept was unclear for a long time, recent studies clarified genetic, clinical, and pathological features [6]. Furthermore, due to the rapid development of comprehensive genetic analysis technique using next-generation sequencing (NGS), it has been revealed that the number of patients with chronic kidney disease (CKD) caused by these gene mutations is far higher than previously expected [9][10][11][12], resulting in ongoing discussions regarding the diagnosis of this condition [13][14][15][16][17]. Here, we review the previous publications regarding TBMN and ADAS and discuss the diagnosis of cases with heterozygous COL4A3 or COL4A4 variants.…”
Section: Introductionmentioning
confidence: 99%
“…NPHS1 gene variants usually lead to a more severe phenotype of congenital nephrotic syndrome; however, some missense variants lead to milder phenotypes, such as in our case [ 14 ]. The overall diagnosis rate was 90% in this study [ 13 ].…”
Section: Overall Genetic Background In Asmentioning
confidence: 82%
“…We recently published the results of genetic testing for AS in Japan [ 13 ]. We conducted Sanger sequencing for 294 suspected AS cases and next-generation sequencing (NGS) for 147 suspected AS cases.…”
Section: Overall Genetic Background In Asmentioning
confidence: 99%
“…However, the results of patients with threonine mutation to methionine do not support Alport syndrome. [17][18][19] Multidrug combination is mainly used to slow progress of disease. Target therapy is expected to change the prospects of IgAN treatment strategies.…”
Section: Discussionmentioning
confidence: 99%